Sunny the rainy, rainy the sunny climate change through the eyes of DOSCST students - Baquiano, Marshaley J. (Davao Research Journal: the official R & D Publication of Davao Oriental State College of Science and Technology, 2014)
The study examined undergraduate students’ social understanding of climate change, using the lens of Social Representation Theory. One hundred thirty-seven students answered a free association questionnaire in which they wrote down their ideas regarding climate change. Climate change is socially perceived as plain modification in the patterns of weather, climate, season, and temperature. A phenomenon that brings both progress and harm. It is viewed as causing the weather to become unpredictable and abruptly changing, similar to a person with mood swings. Climate change is also socially understood to have been caused by human beings’ abusive behaviors towards the environment, resulting to financial, psychological, social, and health problems as well as environmental devastation. Climate change rouses fear and anxiety, leading to a cry for people to take care of the environment. Insights from the study have implications on the creation and implementation of strategies and policies on climate change mitigation and adaptation.